ANALISA IMPLEMENTASI TEKNIK RECONNAISSANCE PADA WEBSERVER (STUDI KASUS: UPT PUSKOM UNIVERSITAS DEHASEN) - Marsoni Marsoni; Toibah Umi Kalsum; Adhadi Kurniawan (UNIVED Press, 2016)
Information on the website is a matter that must be considered. The issue is important because if the information on a website accessible to people who are not responsible for the accuracy of such information would undoubtedly could even be misleading information. Activities to gather information on the web server needed a longer time to the system. This study did reconnaissance to obtain important information on the website, accunetix tool, nmap, nslookup, tcptraceroute can find information about the weaknesses of the website. From these results obtained some important information from the website using the tool. In order to know the complete information on the wireless network in the form of a simulation such as online.Keywords: Reconaissance, webserver, accunetix